Vertical organization of microbial communities in Salineta hypersaline wetland, Spain - Bourhane, Zeina; Cagnon, Christine; Castañeda, Carmen; Rodríguez-Ochoa, Rafael; Álvaro-Fuentes, Jorge; Cravo-Laureau, Cristiana; Duran, Robert (Frontiers in Microbiology, 2023)
Microbial communities inhabiting hypersaline wetlands, well adapted to the environmental fluctuations due to flooding and desiccation events, play a key role in the biogeochemical cycles, ensuring ecosystem service. In order to better understand the ecosystem functioning we studied soils microbial communities of Salineta wetland (NE Spain) in dry and wet seasons in three different landscape stations representing situations characteristic of ephemeral saline lakes: S1 soil usually submerged, S2 soil intermittently flooded and S3 soil with halophytes. Microbial community composition was determined according to different redox layers by 16S rRNA gene barcoding. We observed reversed redox gradient, negative at the surface and positive in depth, which was identify by PERMANOVA as the main factor explaining microbial distribution. The Pseudomonadota, Gemmatimonadota, Bacteroidota, Desulfobacterota and Halobacteriota phyla were dominant in all stations. Linear discriminant analysis effect size (LEfSe) revealed that the upper soil surface layer was characterized by the predominance of operational taxonomic units (OTUs) affiliated to strictly or facultative anaerobic halophilic bacteria and archaea while the subsurface soil layer was dominated by an OTU affiliated to Roseibaca, aerobic alkalitolerant bacterium. Additionally, the potential functional capabilities, inferred by Picrust2 analysis, involved in carbon, nitrogen and sulfur cycles were similar in all samples irrespective of the redox stratification, suggesting a functional redundancy. Our findings show microbial community changes according to water flooding conditions, which represent useful information for biomonitoring and management of these wetlands whose extreme aridity and salinity conditions are exposed to irreversible changes due to human activities.